THE ROLE OF GENDER INCLUSION IN ADDRESSING CLIMATE CHANGE AND ENVIRONMENTAL JUSTICE - Charles Ochieng’ Oguk; Pamela Okong’o (IJRDO - Journal of Social Science and Humanities Research, 2025)
This paper investigates the critical role of gender inclusion in addressing the interconnected challenges of climate change and environmental injustice in Kenya, where existing socio-economic inequalities and gender norms exacerbate environmental vulnerabilities for women and marginalized groups. It argues that the frequent oversight of gender in current approaches hinders effective solutions. Through a qualitative analysis of Kenyan constitutional provisions, national policies (including the National Policy on Gender and Development and the National Climate Change Framework Policy), relevant legislation (such as the Climate Change Act), and scholarly literature, this research examines the gendered impacts of climate change, the vital contributions of women (including indigenous knowledge), and the extent of gender mainstreaming in legal and policy frameworks. Findings reveal significant gender disparities, highlight women’s crucial roles in environmental sustainability, and identify persistent barriers to gender inclusion, such as data gaps and patriarchal norms. The paper underscores the indispensable nature of meaningful gender inclusion for achieving sustainable and just climate action and environmental justice in Kenya. It recommends a paradigm shift towards fully integrating gender considerations into all stages of climate initiatives, advocating for gender-responsive finance, environmental impact assessments, enhanced participation in decision-making, and addressing structural inequalities to build a more resilient and equitable future for all Kenyans